2009
DOI: 10.1186/1471-2407-9-403
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the controversial association of Streptococcus gallolyticus with colorectal cancer and adenoma

Abstract: BackgroundThe seroprevalence of IgG antibodies of Streptococcus gallolyticus subspecies gallolyticus, CIP 105428, was evaluated to investigate the controversial association of S. gallolyticus with colorectal carcinoma and adenoma in attempt to investigate the nature of such association if any, by exploring the mRNA expression of NF-κB and IL-8. Moreover, the serological behavior of S. gallolyticus IgG antibodies was compared to that of an indicator bacterium of bowel, Bacteroides fragilis.MethodsELISA was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 30 publications
(31 reference statements)
4
90
0
Order By: Relevance
“…However, surprisingly, another study (Devis et al, 1989) found that the association between S. bovis/gallolyticus and adenoma was more evident than that with colorectal cancer; they r e p o r t e d t h a t 3 6 % o f p o s i t i v e b l o o d c u l t u r e s o f S. bovis/gallolyticus were found in proliferative lesions (15% of cancers and 21% of adenomas). A recent study (Abdulamir et al, 2009) supported this concept showing that the level of S. bovis/gallolyticus IgG antibodies in adenoma patients is much higher than in both colorectal cancer patients and control subjects. However, other reports did not reveal the same thing.…”
Section: The Association Of Premalignant Colorectal Lesions With S Bmentioning
confidence: 86%
See 4 more Smart Citations
“…However, surprisingly, another study (Devis et al, 1989) found that the association between S. bovis/gallolyticus and adenoma was more evident than that with colorectal cancer; they r e p o r t e d t h a t 3 6 % o f p o s i t i v e b l o o d c u l t u r e s o f S. bovis/gallolyticus were found in proliferative lesions (15% of cancers and 21% of adenomas). A recent study (Abdulamir et al, 2009) supported this concept showing that the level of S. bovis/gallolyticus IgG antibodies in adenoma patients is much higher than in both colorectal cancer patients and control subjects. However, other reports did not reveal the same thing.…”
Section: The Association Of Premalignant Colorectal Lesions With S Bmentioning
confidence: 86%
“…Nevertheless, the relationship between colorectal bacterial infection and the progressive development of malignant disease in pre-neoplastic adenomatous polyps was supported by recent reports (Abdulamir et al, 2009;Kahveci et al, 2010;Murinello et al, 2006). Interestingly, benign lesions (diverticulosis, inflammatory bowel disease, cecal volvulus, perirectal abscess hemorrhoids, benign polyps) were found to be mildly associated with intestinal bacterial infections such as S. bovis/gallolyticus while a strong relationship between more malignant diseases of the colon (cancer and neoplastic polyps) and S. bovis/gallolyticus was found (Abdulamir et al, 2009;Burns et al, 1985;Klein et al, 1979;Nielsen et al, 2007;Reynolds et al, 1983;Smaali et al, 2008). It was also revealed that S. bovis/gallolyticus septicemia and/or endocarditis is selectively related to the presence of villous or tubulovillous adenomas in the large intestine (Fagundes et al, 2000;Smaali et al, 2008).…”
Section: The Association Of Premalignant Colorectal Lesions With S Bmentioning
confidence: 91%
See 3 more Smart Citations